Flowering Plant Diversity of District Karnal, Haryana, India - Ravinder Kaur; Nidhan Singh; Vashistha BD (International Journal of Life Sciences, 2016)
During an extensive study carried out to assess the floristic diversity of the Karnal District, Haryana, 345 angiospermic plants were recorded belonging to 245 genera and 77 families. Out of that, 309 species belong to dicotyledons (218 genera and 69 families), 36 species belong to monocotyledons (27 genera & 8 families). Habit wise grouping shows 196 (56.81%) are herbs followed by 64 (18.55%) trees, 50 (14.49%) shrubs and 35 (10.14%) climbers. Among the families of angiosperms, Fabaceae with 47 species is the dominant family followed by Asteraceae, Poaceae, and Malvaceae. Ipomoea is the dominant genus with 8 species followed by Solanum, Euphorbia, Sida, Cyperus, and Ficus. The present study provides basic information about floristic composition, which will be supportive for management and conservation of the plant wealth of the area. Plants are enlisted with botanical name, family, local name, habit and distributional status of each species.